Cheese: mere indulgence or part of a healthy diet? - Eugénio, Ana; Ramos, Rita; Barreto, Inês R.; Carriço, Raquel; Marcos, Joana; Camelo, Alexandra; Espírito Santo, Christophe; Brandão, Inês (Frontiers in Nutrition, 2025)
Cheese is a widely consumed fermented dairy product with a long history of human consumption dating back several millennia, which justifies a brief historical introduction in this review. Beyond its cultural and gastronomic relevance, cheese presents a complex nutritional and microbial matrix that may confer neutral or even beneficial effects on cardiometabolic health, despite concerns related to its saturated fat and sodium content. This review first explores the key components of the cheese matrix and several mechanisms potentially involved in its metabolic impact, including the presence of polar lipids, the production of short-chain fatty acids (SCFAs) and alpha-linolenic acid (ALA) by the cheese microbiota, and the high calcium content that may reduce fat absorption, among others. Additional bioactive compounds formed during fermentation, such as angiotensin-converting enzyme (ACE)-inhibitory peptides, are also discussed for their potential health effects. We also include a comprehensive survey of most European Protected Designation of Origin (PDO) cheeses and their microbiota. Finally, to assess the most recent evidence in human health, we analyzed a sample of studies published on PubMed in the last 2.5 years, including observational studies and randomized controlled trials. This selection highlights the latest research trends and supports a growing body of evidence suggesting that cheese, particularly in its intact matrix form, is not associated with adverse cardiometabolic outcomes—and may even exert protective effects. These findings call for more robust, long-term trials to confirm causality and support updated dietary guidance.